1994
DOI: 10.3347/kjp.1994.32.1.27
|View full text |Cite
|
Sign up to set email alerts
|

Second report on intestinal parasites among the patients of Seoul Paik Hospital (1984-1992)

Abstract: The results of fecal examination for helminth eggs and protozoan cysts in Seoul Paik Hospital during 1984-1992 are reported. Fecal specimens of a total of 52,552 out- or inpatients were examined by formalin-ether sedimentation and/or direct smear method. The overall egg positive rate of helminths was 6.5% and the cyst positive rate of protozoa 2.5%. The egg positive rate (number of positive cases) for each species of helminth was; Clonorchis sinensis 3.2% (1,667), Trichuris trichiura 2.0% (1,089), Metagonimus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Clonorchiasis is a common infectious disease in Korea. For example, the yearly eggpositive rate for C. sinensis among outpatients nationally ranged from 2.3 to 3.9% between 1984 and 1992 (Lee et al, 1994), indicating the infection of this trematode infection in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Clonorchiasis is a common infectious disease in Korea. For example, the yearly eggpositive rate for C. sinensis among outpatients nationally ranged from 2.3 to 3.9% between 1984 and 1992 (Lee et al, 1994), indicating the infection of this trematode infection in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Routine stool examination methods, such as formalin-ether concentration method and cellophane thick smear, showed that the E. vermicularis infection rate to be 0.1% among the inhabitants in the upper stream of Kumgang (River) and 0.02% among the patients who had visited Seoul Paik Hosptial (Kim et al, 1994;Lee et al, 1994 (Kim et al, 1991). Since the life cycle of the parasite and children's habits affect the control of E. vermicularis, a strict control or extermination of enterobiasis is difficult.…”
mentioning
confidence: 99%
“…A study in Thailand by Peng et al showed that, among the total (1364) stool sample, 18% (245) were positive for one or more parasites and Echinostoma species accounted to 0.1% [ 10 ]. According to Lee et al from Seoul Paik Hospital revealed egg positivity rate of Echinostoma species as 0.03% (12) out of total 53,552 fecal specimens [ 11 ]. An epidemiological survey by Ryang from Korea in 473 junior high school students and 169 inhabitants revealed 3 (0.5%) positive cases of echinostomiasis [ 12 ].…”
Section: Discussionmentioning
confidence: 99%